Determinants of Quality of Life and Treatment Satisfaction During Long-Term Involuntary In-patient Treatment of Dual-Diagnosis Patients - Van Kranenburg, Grieke D.; Diekman, Wout J.; Van den Brink, Rob H. S.; Mulder, Wijnand G.; Pijnenborg, G. H. M.; Mulder, C. L. (Frontiers in Psychiatry, 2022)
Introduction Treatment resistance and disengagement from mental health services are major obstacles in the treatment of dual diagnosis patients with Severe Mental Illness. The patients in this study were admitted to a long-term involuntary treatment facility. Aim of the study To study which patient experiences and perceptions are related to the outcome measures Subjective Quality of Life (SQOL) and Treatment Satisfaction (TS) during the long-term involuntary treatment. Methods Patients were invited for an interview by an independent researcher, which included self-report questionnaires. The structured interviews included self-assessing Helping Alliance, Insight, Attitude towards involuntary admission, Perceived coercion and Perceived benefit were studied as determinants of SQOL and TS. The relationship between the determinants and the outcomes were analyzed by linear regression analysis. Results Patient reported outcomes from dual diagnosis patients in a long-term treatment facility, showed that most of the patients, in spite of the involuntary character of the treatment, were satisfied with the treatment. With respect to the determinants of SQOL and TS the perceptions that “My opinion is taken into account” and “Perceived benefits of the treatment” are strong predictors of both the outcomes. Conclusions The current study shows that the most important aspects for treatment satisfaction and quality of life of dual-diagnosis patients admitted involuntary to long-term treatment, are being listened to (being taken seriously) and experiencing improvements during treatment. These qualities reflect the goals of Shared Decision Making and Perceived Procedural Justice in treatment. The study also corroborates earlier findings that even when treated involuntarily, patients might not hold particular negative views regarding their treatment.